Species Inventory of Epilithic Macroalgae in Padang Unoi Coastal Waters, Simeulue Island - Wahyuni, Sri; Mursawal, Asri; Usiani, Lulu; Kurniawan, Ronal (Jurnal Natur Indonesia, 2025)
Epiphytic macroalgae are phototrophic organisms that attach to rigid substrates in the intertidal zone and serve as key components of coastal ecosystem structure due to their roles in providing habitat, stabilizing substrates, and supporting nutrient cycling. This study aimed to inventory the types of epiphytic macroalgae present in the rocky intertidal zone of Padang Unoi Village, Salang District, Simeulue Regency. Observations were conducted in July 2025 along a 150-m transect, dividing the area into two tidal zones: the lower littoral and the mid-littoral. The inventory revealed seven species of epiphytic macroalgae, namely Turbinaria sp, Sargassum sp, Padina sp, Chaetomorpha aerea, Caulerpa taxifolia, C. racemosa, and Amphiroa subcylindrica. Species from the Phaeophyta division dominated the mid-littoral zone, while Chlorophyta were more abundant in the lower littoral zone, and Rhodophyta were observed on coarse-textured rocky substrates. These three major divisions indicate habitat heterogeneity that supports the growth of various types of epiphytic macroalgae. The results of this study highlight the importance of the rocky intertidal zone of Simeulue as a productive habitat and provide a basis for sustainable coastal resource management